THE DEVELOPMENT OF TELEPON KALENG GAME AS A MEDIA TO STIMULATE LINGUISTIC INTELLIGENCE OF EARLY CHILDHOOD - Betty Yulia Wulansari; Ambiro Puji Asmaroini (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2018)
The aim of this research is to determine the validity of telepon kaleng game as a medium to stimulate the linguistic intelligence of early childhood, as well as to know the merits and drawbacks of telepon kaleng game as learning media. The research method used is research and development (R D). Development procedures include planning, design, and development. Product validation is done by alpha test, beta test, and final evaluation. Apha test is validated by an expert in material development and an expert in teaching-media development. Meanwhile, the subjects in beta test are students BA Aisyiah Yanggong and BA Aisyiah Wonoasri Jenangan District, Ponorogo Regency. The result of this research is the development of telepon kaleng game as a media to stimulate linguistic intelligence of early child. The tools and materials used in this development are used-can, thread / rope, flannel, scissors, and double tape. Material experts and media experts have validated telepon kaleng products developed. From validation, the results need to improve the use of tin cans and the improvement of learning materials. In the next stage, feasibility testing for users in BA 'Aisyiah Yanggong and BA' Aisyiah Wonoasri Jenang Subdistrict of Ponorogo Regency, from the result of the experiment showed that telepon kaleng could be used to stimulate the linguistic intelligence of early child. These telepon kalengs, when used in unlimited form by children, stimulate linguistic intelligence more than IN structured-form. The merit of telepon kaleng as a linguistic intelligence stimulus medium is an attractive form of the child compared totelepon kaleng without any accessories. Children tend to prefer things that are bright and engaging. The drawback of this telepon kaleng, if it is used continuously, is that it will lead to monotonous learning process so it needs to alternate with other game equipment.